77.1k views
3 votes
Solve for t in the following equation. 10t + 4 - 2t = 2-2(t +4)A. t = -1B. t= -3/5C. t= 3/5D. t= 1

User Semao
by
4.8k points

1 Answer

1 vote

Step 1:

Write the equation

10t + 4 - 2t = 2 - 2 ( t + 4)

Step 2:

Use the distributive property to expand the right hand side and collect similar terms.


\begin{gathered} 10t\text{ + 4 - 2t = 2 - 2t - 8} \\ 10t\text{ - 2t + 2t = 2 - 8 - 4} \\ 10t\text{ = -10} \\ \text{Divide both sides of the equation by 10} \\ (10t)/(10)\text{ = }(-10)/(10) \\ t\text{ = -1} \end{gathered}

Final answer

t = -1 Option A

User Jeninja
by
4.8k points